2014
DOI: 10.1136/neurintsurg-2014-011271
|View full text |Cite
|
Sign up to set email alerts
|

Angiographic factors influencing the success of endovascular treatment of arteriovenous malformations involving the corpus callosum

Abstract: AVMs of the corpus callosum seems to be difficult to treat with endovascular therapy alone. The goal of embolization should be prevention of (re) bleeding and a decrease in nidus size. Our experience regarding this sub-pathology suggests that a combination of endovascular therapy and radiotherapy may be the best option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…The complication rate associated with these procedures ranges from 5% to 20%. [ 37 39 49 ] Our analysis of the literature revealed that fifty patients underwent standalone endovascular embolization of the AVM and cure was achieved in only 20 (40%), similar to the results noted by Picard et al . Only four patients underwent presurgical embolization of their AVMs, of which 3 (75%) were completely excised.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The complication rate associated with these procedures ranges from 5% to 20%. [ 37 39 49 ] Our analysis of the literature revealed that fifty patients underwent standalone endovascular embolization of the AVM and cure was achieved in only 20 (40%), similar to the results noted by Picard et al . Only four patients underwent presurgical embolization of their AVMs, of which 3 (75%) were completely excised.…”
Section: Discussionsupporting
confidence: 84%
“…No prospective cohorts or randomized studies were found. [ 2 3 4 5 6 8 10 11 12 15 16 17 18 19 20 21 23 24 25 26 27 28 29 30 31 32 33 34 37 38 39 40 41 42 47 48 50 53 54 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The number and diameter of feeding arteries, nidal volume, deep venous drainage, and eloquent location were risk factors of embolization-related complications ( 47 , 54 , 55 ). When disposing of bAVMs in corpus callosum with complex angioarchitectures and eloquence involved, curative embolization achieved complete obliteration in only 40–60% of cases and hemorrhage complications occurred in 7% of cases ( 197 , 198 ).…”
Section: Resultsmentioning
confidence: 99%
“…1 Resection of callosal AVMs presents unique challenges because of their deep location; proximity to critical structures, such as the fornices and internal cerebral veins; and often-dense beds of arterial feeders arising from the distal anterior cerebral artery and its branches. [1][2][3][4] This operative video shows complete resection of a complex, high-grade AVM involving the entire corpus callosum of a teenage woman who presented with headache and decreased level of consciousness. Head computed tomography findings included intraventricular hemorrhage; follow-up computed tomography and digital subtraction angiography confirmed a pancallosal AVM, classified as Spetzler-Martin grade IV (size, 2; deep drainage, 1; eloquence, 1) and Lawton-Young grade I (age, 1; bleeding, 0; compactness, 0), with a supplemented grade of 5.…”
mentioning
confidence: 99%